BOCCIA'S TEACHING FOR TEENAGERS WITH CEREBRAL PARALYSIS (Fiep Bulletin - online, 2014)
The boccia is a sporty modality that was adapted for people with cerebral paralysis and our objective with that article is to present how it is possible to create opportunities for these cerebral paralyzed through boccia teaching, enabling to these students the pleasure by its practice. To make this work noticed for a month 6 students with cerebral paralysis verifying their performances during boccia practice, students with age between 12 to 18 years that went to the Program of Motive Activities for Deficient (PROAMDE) in year of 2007. With that work we concluded that even with his motor limitations the students made an effort to guarantee a good result in the game, respecting and showing the basic knowledge of the rules.
Keywords: Boccia; Cerebral Paralysis; Physical Education